Instructional strategies for the differentiated classroom - Kiernan, Leslie J.; Frost, Frank; Association for Supervision and Curriculum Development (Alexandria, VA : ASCD, 2003)
Each video takes teachers through the process of planning and using the four strategies--learning contracts, intelligence preferences, tiered assignments, and complex instruction--to address learning standards and desired outcomes. Commentary from Carol Ann Tomlinson and classroom teachers explains why the strategy is used, what impact it has on kids, and offers tips and cautions for each strategy
tape 1. Learning contracts (27 min.) -- tape 2. Intelligence preferences (24 min.) -- tape 3. Tiered assignments (36 min.) -- tape 4. Complex instruction (43 min.) -- tape 5. RAFT assignments (40 min.) -- tape 6. Centers (35 min.) -- tape 7. WebQuest (37 min.) --
Title from title screen
Copy available in DVD format
Camera, Richard Diamond ; graphic artists, Reece Quiñones, Shane Baker ; editor, Judith E. Herbert ; sound, ick Patterson, William Kaplan
Consultant: carol Ann Tomlinson
Keywords: Individualized instruction; Cognitive styles in children; Mixed ability grouping in education